2022
DOI: 10.1161/jaha.121.023219
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Smartwatch Facilitated Remote Health Management for Patients Undergoing Transcatheter Aortic Valve Replacement

Abstract: Background In the recent decades, the development of novel digital health technologies enables doctors to monitor ECG and vital signs remotely. But the data on applying the noninvasive wearable smartwatch on patients with transcatheter aortic valve replacement (TAVR) are unknown. Methods and Results We performed a prospective, observational cohort study to evaluate the feasibility of a novel, virtual, and remote health care strategy for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…[36]. Smartwatches with similar functions of single-lead ECG collection have also been reported in other brands, such as Apple Watch and Huawei Smartwatch [10,23]. The telecare function of smartwatch might be especially demanded during the COVID-19 pandemic nowadays to overcome the difficulty in achieving in-site outpatient assessment.…”
Section: Smartwatch For Remote Health Care In the Tavr Populationmentioning
confidence: 84%
“…[36]. Smartwatches with similar functions of single-lead ECG collection have also been reported in other brands, such as Apple Watch and Huawei Smartwatch [10,23]. The telecare function of smartwatch might be especially demanded during the COVID-19 pandemic nowadays to overcome the difficulty in achieving in-site outpatient assessment.…”
Section: Smartwatch For Remote Health Care In the Tavr Populationmentioning
confidence: 84%
“…Our previously published data showed that the step count in patients after TAVR progressively increased within 1 month. 9 In this study, we have identified the median step of 3069 (IQR, 1830-5028) among 222 patients within the first month after TAVR. It was consistent with previous pilot studies monitoring PA in 10 patients after TAVR using wearable activity trackers, such as the Fitbit-Flex (Fitbit, Inc, San Francisco, CA).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information for the cohort has been published elsewhere. 9 Briefly, the registry started in July 2020 and consecutively recruited patients undergoing elective transfemoral TAVR. Participants were provided with a smartwatch (Huawei Watch GT 2 Pro ECG edition) to record their health information including daily activity, heart rate, pulse oxygen saturation, and single-lead ECG.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies investigated TIM in AS patients undergoing TAVI. The studies focused mainly on the detection of conduction disturbances after TAVI and the need for pacemaker implantation ( 19 , 20 ). In the prospective cohort study Redirect TAVI, continuous pocket electrocardiograms were used to detect conduction disturbances in 192 AS patients without pacemakers 14 days before and after TAVI ( 19 ).…”
Section: Discussionmentioning
confidence: 99%